Long-term effectiveness of the Diabetes Conversation Map Program: A prepost education intervention study among type 2 diabetic patients in Taiwan. Issue 36 (September 2017) - Hung, Jui-Yu; Chen, Pin-Fan; Livneh, Hanoch; Chen, Yi-Yu; Guo, How-Ran; Tsai, Tzung-Yi
Abstract : Abstract: Health education is compulsory for patients with chronic and life-threatening disease, especially for those with diabetes mellitus (DM). This study aimed to examine the long-term effectiveness of the Diabetes Conversation Map Program (DCMP) among DM patients in Taiwan. A quasi-experimental research design using convenience sampling and nonrandom group assignment was applied to recruit 95 type 2 diabetic subjects from a hospital in Taiwan. In addition to routine care, the experiment group (n = 49) received 7 sessions of DCMP that delivered over 2 months, while the control group (n = 46) received only routine care during the same period. We conducted structured questionnaire survey and reviewed medical record at 3 time points (before DCMP, 3 days after DCMP, and 3 months after DCMP completion) to collect the effectiveness data. The effectiveness was determined using the generalized estimating equation model. We found that improvements in the body mass index, blood glucose, glycated hemoglobin, self-monitoring of blood glucose, and diabetic health literacy in the DCMP group compared with controls (all P values <.05), with no significant changes in depressive symptoms. The positive effects were further maintained for 3 months after DCMP. The findings may serve as a reference for helping healthcare professionals provide appropriate interventions to improve adaptation processes and clinical outcomes for DM patients.